Influence of Dielectric Constants on Complex Equilibria of Cu(II)-Salicylic Acid Complexes in Different Percentages of Methanol-Water Mixtures - Kirnapure, K.T.; Khobragade, B.G. (Asian Journal of Chemistry, 2010)
The interaction between Cu(II) and salicylic acid in different percentages of methanol-water mixtures at 0.1 M ionic strength has been studied pH-metrically at the temperature 29 ± 0.1ºC. The data are used to study the values of proton-ligand and metal-ligand stability constants for 1 : 1 and 1 : 2 complexes. In the present investigation, the effect of dielectric constants on stability constants of complex equilibria is studied.